Relationship between the Application of ICT and Record Keeping Management in Federal Universities in Northern Nigeria - Maxwell, Ochade; Babagana, Muhammad (NIU Journal of Humanities, 2024)
This study explores the relationship between the application of Information and Communication Technology (ICT) and record-keeping management in Federal Universities of Northern Nigeria.  The research employs a correlational research design, utilizing correlational analysis to measure the statistical relationship between ICT application and record-keeping management. The study encompasses all Federal Universities in Northern Nigeria, with a sample size of 2,114 selected through a proportional sampling method across three geopolitical zones. Demographic characteristics of the respondents, including age, years of experience, qualification, and gender, are presented, providing insights into the diverse composition of the sample. The study employs a four-point Likert Rating Scale and Pearson's Product Moment Correlation coefficient for data analysis. Results indicate a significant positive correlation between the application of ICT and general record-keeping management, leading to the rejection of the null hypothesis. The discussion highlights the profound relationship between ICT and record-keeping management, showcasing the benefits of digital archiving, data security, accessibility, and advanced data analysis. The findings contribute to the understanding of how ICT tools and applications are transforming records management practices in higher education. The study concludes with a discussion on the importance of integrating ICT for preserving institutional heritage, ensuring data security, and fostering compliance with data protection regulations. Recommendations include Federal Universities should prioritize investment in advanced ICT infrastructure to ensure that their systems can effectively support record-keeping management. Up-to-date hardware and software are essential for the seamless operation of Human Resource Information Systems (HRIS) and other ICT tools. Keywords : Application of ICT Integration; Record Keeping Management; Human Resource Information Systems (HRIS)